Influence of Multi-Frequency Ultrasound-Assisted Freezing on the Freezing Rate, Physicochemical Quality and Microstructure of Cultured Large Yellow Croaker (Larimichthys crocea) - Ma, Xuan; Mei, Jun; Qiu, Weiqiang; Xie, Jing (Frontiers in Nutrition, 2022)
The purpose of this work was to investigate the influence of multi-frequency ultrasound-assisted immersion freezing (UIF) on the freezing speed, quality attributes, and microstructure of cultured large yellow croaker (Larimichthys crocea) with different ultrasound powers. The findings revealed that UIF under multi-frequency conditions greatly enhanced the speed of food freezing and shortened the freezing time. The multi-frequency UIF reduced the thawing and cooking losses, total volatile base nitrogen, K values and thiobarbituric acid reactive substances values, and increased the water holding capacity. The microstructure observation showed that multi-frequency UIF at 175 W reduced pore diameter and ice crystal size. Free amino acids analysis revealed that the application of multi-frequency UIF reduced the accumulation of bitter amino acids, and UIF-175 treatment increased the accumulation of umami amino acids. Therefore, multi-frequency UIF at suitable ultrasonic power remarkably improved the quality attributes of large yellow croaker.